A validation of the 4S-AF scheme in Spanish and French patients from the EORP-AF Long-Term General Registry. (24th May 2021) - Rivera-Caravaca, JM; Piot, O; Roldan-Rabadan, I; Denis, A; Anguita, M; Mansourati, J; Marijon, E; Leclercq, C; Garcia-Bolao, I; Lellouche, N; Potpara, T; Boriani, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): Abbott Vascular Int. (2011–2014), Amgen Cardiovascular (2009–2018), AstraZeneca (2014–2017), Bayer AG (2009–2018), Boehringer Ingelheim (2009–2019), Boston Scientific (2009–2012), The Bristol Myers Squibb and Pfizer Alliance (2011–2016), The Alliance Daiichi Sankyo Europe GmbH and Eli Lilly and Company (2011–2017), Edwards (2016–2019), Gedeon Richter Plc. (2014–2017), Menarini Int. Op. (2009–2012), MSD-Merck & Co. (2011–2014), Novartis Pharma AG (2014–2017), ResMed (2014–2016), Sanofi (2009–2011), SERVIER (2009–2018). The Atrial Fibrillation NETwork (AFNET), conducting the registry in Germany, received support from The Bristol Myers Squibb/Pfizer Alliance (2014–2018) and the German Centre for Cardiovascular Research (DZHK). Funding from Daiichi-Sankyo and Boehringer-Ingelheim have been received for conducting the registry in Spain. Funding from BMS-Pfizer Alliance was received to support the programme in France Background: The 4S-AF scheme (Stroke risk, Symptom severity, Severity of atrial fibrillation [AF] burden, Substrate severity) has recently been described as a novel approach to in-depth characterization of AF, and included in the 2020 European Society of Cardiology guidelines for the management of AF. Purpose: In the present study, we validated for the first time the 4S-AF scheme in the Spanish and French cohorts of the EurObservational Research Programme (EORP)-AF Long-Term General Registry. Methods: The Spanish and French cohorts of the EORP-AF Long-Term General Registry, were merged and included. The baseline 4S-AF scheme was calculated as follows: Symptom severity (according to EHRA symptom score: 0-2 points), Severity of AF burden (according to AF type: 0-3 points), Substrate severity (according to comorbidities/cardiovascular risk factors: 0-7 points); and related to the primary management strategy (rhythm or rate control). According to the results for these 3 domains, four code colors have been defined. Patients with all domains in "green" should be managed by rhythm control. In patients with one domain in "yellow" or two domains in "green" categories, rhythm control can be attempted. On contrary, for patients with "red" color category, the 4S-AF scheme suggests a rate control strategy. All-cause mortality and the composite of ischemic stroke/transient ischemic attack/systemic embolism, major bleeding and all-cause death, were the primary endpoints. These outcomes were recorded during 1-year of follow-up. Results: 1479 patients (36.9% females, median age of 72 [IQR 64-80] years) were included (Table 1). The median 4S-AF scheme score was 5 (IQR 4-7). The 4S-AF scheme, as continuous and as categorical, was associated with the management strategy decided for the patient (both p < 0.001). The predictive performances of the 4S-AF scheme for the actual management strategy were appropriate in its continuous (C-index: 0.77, 95% CI 0.75-0.80) and categorical (C-index: 0.75, 95% CI 0.72-0.78) forms (Figure 1A). Cox regression analyses showed that patients classified as "red" category in the 4S-AF scheme had higher risk of all-cause death (adjusted HR 1.75, 95% CI 1.02-2.99) and composite outcomes (adjusted HR 1.60, 95% CI 1.05-2.44) (Figure 1B). Thus, patients for who the 4S-AF scheme suggests that may be managed by rhythm control (recommended or considered) had a significantly lower risk of these events. Conclusion: Characterization of AF by using the 4S-AF scheme may aid in identifying AF patients that would be managed by rhythm or rate control, and could also help in identifying high-risk AF patients for worse clinical outcomes in a 'real-world' setting.